Epithelial cell proliferation in the rectal stump of patients with ileorectal anastomosis for ulcerative colitis. Issue 11 (November 1983) - Lehy, T; Mignon, M; Abitbol, J L
Abstract : Epithelial cell proliferation in the rectal stump after ileorectal anastomosis for ulcerative colitis was studied in 19 patients. This was achieved through in vitro incorporation of tritiated thymidine in mucosal biopsies and radioautographic analysis of the number and position of labelled nuclei in the crypts. Rectal biopsies from nine unoperated patients with ulcerative colitis and from 10 controls, were processed simultaneously. Except for one, all patients were clinically in remission. The crypt length and number of labelled cells per crypt column were found to be similar in the rectal mucosa from the three groups of subjects. The mean labelling index, although low 8.9%, was higher (p less than 0.05) in operated patients compared with controls; but the dispersion of individual values was similar in both groups. There was an extension of the proliferative compartment towards the surface in 88% of unoperated patients and in 60% of operated patients. In addition, there was a shift of the major zone of proliferation from the lower to the middle third of the crypt in 17% of operated patients and from the lower to the upper third of the crypt in 14% of unoperated patients. No correlation was found between the labelling index and either the age of patient, the duration of disease or the period elapsed after ileorectal anastomosis. Interestingly, among operated patients with a colitis for over 10 years, 42% had a quite normal proliferative pattern with a corresponding mean postoperative period of 7.5 years.